1990
DOI: 10.1073/pnas.87.22.8721
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in genetic variants of human serum albumin found in Italy.

Abstract: A long-term electrophoretic survey of genetic variants of serum albumin has identified an alloalbumin in 589 unrelated individuals in Italy. The alloalbumins were classified electrophoretically into 17 types. The number of unrelated carriers for each type varied from 1 for several variants reported here to 103 for albumin B. The structural change in 8 of these types has previously been determined, and the amino acid substitutions in 3 additional types are reported here. Albumin Varese has a substitution, -2 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
(55 reference statements)
0
28
0
Order By: Relevance
“…Furthermore, we were intrigued by the fact that two rare naturally occurring HSA variants exist with single amino acid substitutions within the DI loops (38,39). We expressed these as recombinant molecules and demonstrated that they bound with reduced FcRn affinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we were intrigued by the fact that two rare naturally occurring HSA variants exist with single amino acid substitutions within the DI loops (38,39). We expressed these as recombinant molecules and demonstrated that they bound with reduced FcRn affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these are missense mutants in which a single nucleotide change resulted in an amino acid substitution within the Dl loops; one in loop I (Vibo Valentia, E82K), and one in loop II (Yanomama-2, R114G) (38,39). We produced these two variants as recombinant GST-fusions that migrated with a profile similar to WT HSA (Fig.…”
Section: Competesmentioning
confidence: 99%
“…Nor has it been reported in Sweden, where about one million electrophoretic analyses have been made (Carl-Bertil Laurell, personal communication). The paradox is that the albumin gene is subject to many neutral mutations (11)(12)(13)(14)(15)(16)); yet, analbuminemia, though tolerable, is extremely rare. It has been postulated (17) that the presence of albumin may be critical in fetal life and only a few analbuminemic individuals survive past the neonatal state; this could explain why analbuminemia is so rare in adults.…”
mentioning
confidence: 99%
“…In addition, four cases of unrelated subjects with analbuminemia have been found. Our laboratories have previously identified the molecular defect in 19 of the 28 variants and in two cases of analbuminemia [3,4,[6][7][8][9][10][11][12][13][14]. Here we report the structural characterization of four Italian alloalbumins, albumins Tregasio, Bergamo, Maddaloni, and Besana Brianza.…”
mentioning
confidence: 91%